Inter-correlation between Sunspot Oscillations and Their Internal Structures. (1st November 2022) - Fu, Libo; Zhu, Zizhan; Yuan, Ding; Wang, Jiaoyang; Feng, Song; Anfinogentov, Sergey
Abstract: Three- and five-minute oscillations are commonly observed in any sunspot. Because they are modulated by the internal thermal and magnetic structures of a sunspot, they could be used as an effective tool for researching sunspot seismology. In this paper, we investigate the properties of oscillations in sunspot groups with varying sizes and magnetic fields, and aim to establish the relationships between sunspot oscillations and its internal structure comparatively. We selected three groups of the unipolar sunspot with approximately axial-symmetric magnetic field and calculated their Fourier spectra based on the ultraviolet/extreme ultraviolet emission intensity variations recorded by the Solar Dynamics Observatory/Atmospheric Imaging Assembly. We found that the distribution of three-minute oscillation is defined by the joint effect of diverging magnetic field and the stratification of the sunspot atmosphere. Its distribution could be modified by any invading magnetic structures in the umbra. In contrast, the five-minute oscillations are more prominent in small spots, implying that five-minute oscillation is very closely connected with umbral dynamics.